Bitter Gourd (Momordica charantia) Peroxidase in Decolorization of Dyes from Tannery Effluent - Ramesh, Kuppuswamy Kavitha, Venkatesan Gopalakrishnan, Vasu Kanniyappan, Subramaniam Sivakumar, Balasubramaniam (Recent Research in Science and Technology, 2010)
Bitter Gourd (Momordica charantia) is a commonly available plant in India and its applications are limited to few medicinal properties in addition to being edible. The primary objective of this study is to evaluate the efficacy of Momordica charantia peroxidase in the degradation of dyes present in tannery effluents under various experimental conditions like pH, Temperature, Time intervals and Enzyme concentration on the basis of the one-factor-at-a-time (OFAT) method. The maximum decolorization was achieved at pH 5.0 – 6.0, 40oC temperature, in 4 hours with an enzyme concentration of 0.6 ml consisting of 4500 Units enzyme activity extracted from 0.5 g of Bitter Gourd. Present study results demonstrate that the Momordica charantia peroxidase is an effective biocatalyst for the treatment of effluents with dyes from tanning industries.